Cascaded H-Bridge MLI and Three-Phase Cascaded VSI Topologies for Grid-Connected PV Systems with Distributed MPPT - Abdullah M. Noman; Khaled E. Addoweesh; Ayman A. Alabduljabbar; Abdulrahman I. Alolah (International Journal of Photoenergy)
Cascaded multilevel inverter topologies have received a great deal of attention for grid-connected PV systems. In this paper, three-cascaded multilevel inverter configurations are proposed for grid-connected PV applications. These are the three-phase cascaded H-bridge multilevel inverter topology, three-phase cascaded voltage-source inverter topology using inductors, and three-phase cascaded voltage-source inverter topology using coupled transformers. Distributed maximum power point tracking (MPPT) of PV modules using perturbation and observation algorithm is used for all presented topologies. In all presented configurations, each PV module is connected to one DC-DC isolated Ćuk converter for best MPPT achievement. Simulation is achieved by using the SIMULINK environment. The simulation results show that the three proposed topologies function well in improving the grid’s power quality. The grid currents are kept in phase with the grid voltage to ensure unity power factor, and the THD of the grid currents are within the acceptable range. The proposed topologies are experimentally implemented in the lab, and the switching pulses are generated with the help of the MicroLabBox data acquisition system. Comparing the three topologies according to the number of switches, voltage, and current stresses on switches and THD of the generated voltages and grid currents and according to the efficiency has been achieved in this paper, both experimentally and by simulation. The simulation and experimental results and comparisons are presented to verify the proposed topologies’ effectiveness and reliability.